2011
DOI: 10.1021/ed1008624
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in Microfluidic Channels

Abstract: General chemistry introduces principles such as acid−base chemistry, mixing, and precipitation that are usually demonstrated in bulk solutions. In this laboratory experiment, we describe how chemical reactions can be performed in a microfluidic channel to show advanced concepts such as laminar fluid flow and controlled precipitation. Three sets of solution-pairs are explored: (i) a visualization of laminar flow at the interface between two dye-colored fluid streams; (ii) an acid−base reaction at the fluid−flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…5 Students printed their device designs onto the polystyrene film using a standard laser printer, cut out rectangular sections containing their design with scissors, and applied heat to shrink the film (for detailed instructions and lesson plan, please see the Supporting Information). As the film shrinks, the lateral size of the pattern is reduced by ~5/8, the height of the ink and the thickness of the polymer increases, and bas-relief features of ink form, whose height can range from approximately 50 to 100 μ m. 5 The previously developed procedure for preparing Shrinky Dink microfluidic devices 3,5,8 was modified, as we found that polystyrene film shrinks more rapidly and evenly when submerged in hot oil than when baked in an oven. After incubating the film for 30 s in a beaker containing vegetable oil warmed on a hot plate, students remove the film with forceps and press it gently between two glass plates to keep it flat as it cools and becomes stiff.…”
Section: Experimental Overviewmentioning
confidence: 99%
“…5 Students printed their device designs onto the polystyrene film using a standard laser printer, cut out rectangular sections containing their design with scissors, and applied heat to shrink the film (for detailed instructions and lesson plan, please see the Supporting Information). As the film shrinks, the lateral size of the pattern is reduced by ~5/8, the height of the ink and the thickness of the polymer increases, and bas-relief features of ink form, whose height can range from approximately 50 to 100 μ m. 5 The previously developed procedure for preparing Shrinky Dink microfluidic devices 3,5,8 was modified, as we found that polystyrene film shrinks more rapidly and evenly when submerged in hot oil than when baked in an oven. After incubating the film for 30 s in a beaker containing vegetable oil warmed on a hot plate, students remove the film with forceps and press it gently between two glass plates to keep it flat as it cools and becomes stiff.…”
Section: Experimental Overviewmentioning
confidence: 99%
“…Microfluidic technology involves the manipulation of fluids in channels at length scales of less than a millimetre, enabling the use of smaller quantities of reagents, high throughputs, low costs and smaller footprints (Haswell and Watts 2003). This has found use in chemical synthesis (Elvira et al 2013;Chia et al 2011;Garcia-Egido et al 2002) and in the biological sciences (Woolley and Mathies 1994;Srinivasan et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…33 While some of the mentioned tools and methods are convenient and powerful in a research environment, to our knowledge, very few educational approaches to microfluidics are available. Some setups employing shrinky-dinks, 34 Jell-O chips, 35 and PDMS 36 have been proposed for classroom usage. Even given the availability of some fast prototyping and production methods, we note that quickly made devices are, even in well-equipped laboratories, still scarce albeit microfluidics will eventually be widely used in many labs.…”
Section: Introductionmentioning
confidence: 99%